2003
DOI: 10.1046/j.1471-4159.2003.02196.x
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid‐β‐induced toxicity of primary neurons is dependent upon differentiation‐associated increases in tau and cyclin‐dependent kinase 5 expression

Abstract: It has previously been reported that amyloid-b (Ab) peptide is neurotrophic to undifferentiated but neurotoxic to differentiated primary neurons. The underlying reasons for this differential effect is not understood. Recently, the toxicity of Ab to neurons was shown to be dependent upon the activation of cyclindependent kinase 5 (Cdk5), thought to promote tau phosphorylation that leads to cytoskeletal disruption, morphological degeneration and apoptosis. Here we report that Cdk5, tau, and phosphorylated-tau (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 93 publications
(191 reference statements)
3
61
1
Order By: Relevance
“…Aβ injection also resulted in the striking hyperphosphorylation of the remaining tau at Ser396 (Fig. 9a, c; +135 %, p=0.002, 2-tailed t test), a site linked with AD pathology, confirming a response to Aβ challenge that has been previously reported [1,23,32]. An attenuated (but significantly) decrease in tau was observed in 12-month-old WT mice injected with Aβ ( Fig.…”
Section: Tau and Phosphorylated Tau Levels In Aβ-injected Hippocampussupporting
confidence: 84%
See 1 more Smart Citation
“…Aβ injection also resulted in the striking hyperphosphorylation of the remaining tau at Ser396 (Fig. 9a, c; +135 %, p=0.002, 2-tailed t test), a site linked with AD pathology, confirming a response to Aβ challenge that has been previously reported [1,23,32]. An attenuated (but significantly) decrease in tau was observed in 12-month-old WT mice injected with Aβ ( Fig.…”
Section: Tau and Phosphorylated Tau Levels In Aβ-injected Hippocampussupporting
confidence: 84%
“…Proponents of the amyloid cascade hypothesis posit that Aβ recruits tau protein as a downstream effector of toxicity. Aβ-induced cytotoxicity was shown to be tau-dependent in primary neuronal culture: the neurons are protected when tau is lowered by either genetic ablation [knockout (KO)], or by leaving them undifferentiated (where they express lower tau levels than differentiated neurons) [1,2]. Ex vivo studies of tau KO neurons revealed that the Aβ-induced axonal transport deficits and impairment of hippocampal long-term potentiation were mediated by tau [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Since this decrease was only partial, we can speculate that there are other cell death pathways acting simultaneously and independently from Cdk5, and thus not inhibited by roscovitine (Agostinho et al 2003;Ferreiro et al 2006). Although several other studies have shown that Cdk5 mediates the neurotoxicity triggered by Abpeptides (Alvarez et al 2001;Liu et al 2004), this is the first study showing that Cdk5 is in part responsible for the neurotoxic effect of PrP. In our experimental conditions, PrP 106-126 and Ab 1-40 did not affect Cdk5 levels (Fig.…”
Section: Discussionmentioning
confidence: 48%
“…Interestingly, Aβ-induced cytotoxicity was shown to be tau-dependent in primary neuronal culture with either genetic depletion of tau, or using an undifferentiated neuronal culture (which has a lower tau level than differentiated neurons) [56,57]. Tau knockout studies revealed that the Aβ-induced axonal transport deficits and impairment of hippocampal LTP were mediated by tau [58,59].…”
Section: Challenges In Targeting Amyloidmentioning
confidence: 99%